Sustainable replacement of asbestos ceiling boards with boards produced from rice husk-marble dust-polystyrene matrix - Abdulganiyu Sanusi; Emmanuel Eberechukwu Ndububa; Adekunle Akanni Adeleke; Edwin Reuben Ade; Ifeyinwa Ijeoma Obianyo; Idris Mohammed; Olaolu Oyinlola Bilewu (Discover Materials)
Abstract Asbestos has been associated with severe health risks, including asbestosis, mesothelioma, and lung cancer, raising major public health concerns. This study explores a sustainable alternative by developing marble-rice husk ceiling boards (MRCB) from rice husk and marble dust, using polystyrene glue derived from waste polystyrene dissolved in premium motor gasoline as a bonding agent. The samples were evaluated for water absorption, fire resistance, nail pull-out strength, and microstructural properties in accordance with the American Society for Testing and Materials (ASTM) and British standards. Among the formulations, MRCB-02, composed of 40% polystyrene glue, 30% rice husk, and 30% marble dust, exhibited the lowest water absorption of 19.86% and maintained structural integrity after 60 min of immersion. The microstructural analysis confirmed uniform material distribution, enhancing mechanical stability. All samples demonstrated strong nail pull-out resistance, while fire resistance tests showed durability against a 20-minute fire exposure, providing crucial evacuation time during fire incidents. These findings highlight MRCB-02 as a promising eco-friendly alternative to asbestos ceiling boards, offering improved safety, durability, and sustainability.